Single cell Li-Ion polymer battery charge and discharge characterizations for application on solar-powered unmanned aerial vehicle - Rajendran, Parvathy; Mazlan, Nurul Musfirah; Smith, Howard (Trans Tech Publications, 2017)
Solar-powered UAV is an alternative way to achieve high endurance and long range UAV flight. However, solar irradiance is not always available during the flight. Thus, secondary power source which is electrical batteries will improve the performance of solar-powered UAV when solar irradiance is not available. Therefore, bench test for LiPo battery is conducted in this paper for the design of solar-powered UAV power system. The impact of operating temperature at various charging and discharging rate on the duration to full charge and discharge and capacity level of a single LiPo battery were assessed. The solar module installed in solar-powered UAV developed by Aircraft Design Group, Cranfield University has to be designed to charge the battery pack at a nominal or maximum rate of 0.129 C and 0.155 C correspondingly. The solar module requires roughly 5.73 hours on nominal charging rate on 30 °C operating temperature to fully charge capacity level instead of 5.54 hours theoretical predicted. The battery pack will then discharge at cruise flight roughly about 0.071 C to a maximum of 1.685 C if required. If the battery pack is not charged, during cruise flight the battery capacity will deplete completely at about 6.51 hours for the same operating temperature, in contrast to the 6.48 hours based on the theoretical prediction. In addition, the usage of LiPo batteries for operation at high altitudes and/or extreme temperatures without an additional heating or cooling system for these battery packs is not favorable. Thus, it is best to charge at low charging rate and high operating temperature to store and utilize the most capacity from this battery.
Keywords: Battery Testing; Cumulative Current; LiPo; LiPo Capacity; Solar-Powered UAV; UAV